OF TEACHING LINGUISTICS USING DIGITAL TECHNOLOGIES - A. M. Aytmuratov (American Journals, 2022)
Today in Uzbekstan and Karakalpakstan there is an active spread of digital technologies in all spheres of life of modern society. they define new approaches to the quality of public and private life, opening up new possibilities and meeting new challenges. This article considers the problem of the formation of innovative competence of future teachers based on digital technologies. The content of the concept of "innovative competence of the future teacher" is specified as a component of professional competence, which ensures the innovative level and quality of the educational process, the embodiment of the actual and potential abilities of its subjects.
Keywords: reflection, competence, reflective competence, development of reflective competence